The closing process of the ductus arteriosus connecting the left common carotid artery and main pulmonary artery. (11th February 2019) - Matsuo, Kumiyo; Aoki, Hisaaki; Kayatani, Futoshi
Abstract: An isolated left common carotid artery is very rare, and only 13 cases have been reported thus far. All those cases were accompanied by a right aortic arch and aberrant left subclavian artery, and the connecting vessel between the pulmonary artery and left common carotid artery was thought to be ductal tissue. However, there have been no reports that have followed the natural closure of this vessel. We present a case in whom we could observe the closing process of this vessel at the connection between the left common carotid artery and main pulmonary artery in association with a tetralogy of Fallot.